A postmodernist reading of Sam Shepard's True West - Joodaki, Abdol Hossein; Shooshtarian, Samaneh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This paper attempts to render some vivid postmodernist features in Shepard's True West (1980), which is inspired by myths of American life and popular culture. Shepard's True West suggests so many interesting postmodern elements. With a departure from conventional norms of character, dialogue and narrative; the elements of pastiche, subjective irony, and savage humor have become hallmarks of most of his works. These features and some of the basic traces of postmodern literature, including Lyotard’s theory of the end of meta-narratives and language game, Derrida’s deconstruction and Baudrillard’s simulation, as well as language fragmentation, uncertainty and duality, altogether, have given Shepard's True West a postmodern atmosphere.